CHARACTERISTICS OF MARINE ENVIRONMENTAL GEOCHEMISTRY FROM HA TINH TO QUANG NAM (60-100M WATER DEPTH) - Huy*, Luong Le; Nhuan, Mai Trong; Quy, Tran Dang; Tuan, Hoang Van; Dat, Quach Manh; Hoai, Nguyen Duc; Tue, Nguyen Tai (Vietnam Journal of Earth Sciences, 2016)
The aim of this study is to elucidate the characteristics of marine environmental geochemistry from Ha Tinh - Quang Nam (60-100m water depth) based on analysis of geochemical parameters of seawater and surface sediments. Surface sediments that are high in absorbed capacity of toxic substances mainly accumulated in northern study area. Seawater dominantly characterized by weak alkaline-weak oxidation and contained biodegradable organic materials. Almost anion and chemical element concentrations in seawater tended to decrease with depth, with an exception for SO42-, Br-, I- concentrations that had an opposite trend, increasing with depth and B, Hg concentrations displayed a complex variation. Sedimentary environments were highly predominant by weak alkaline-strong oxidizing features and carbonate-rich materials. Concentrations of anions and chemical elements tended to be higher in central area in comparison to northern and southern regions, and positively correlated with fine sediment compositions. Organochlorine pesticides (OCPs) concentration decreased with sediment depth, whilst polychlorinated biphenyls (PCBs) concentration had no clear trend. The organic material, heavy metal, OCPs and PCBs concentrations in seawater and sediments were all lower than environmental standards. The present results have provided important baseline data for monitoring marine environment quality and protecting the marine ecosystem of Ha Tinh - Quang Nam Sea. References Addo, M.A., Okley, G.M., Affum, H.A., Acquah, S., Gbadago, J.K., 2011. Water Quality and Level of Some Heavy Metals in Water and Sediments of Kpeshie Lagoon, La-Accra, Ghana. Journal of Environment and Earth Science, 3, 487-497. Aderinola, O.J., Clarke, E.O., Olarinmoye, O.M., Kusemiju, V. and Anatekhai, M.A., 2009: Heavy metals in surface water, sediments, fish and perwinkles of Lagos Lagoon: American-Eurasian journal of agricultural & environmental sciences, 5(5), 609-617. Buccolieri A., Buccolieri, G., Cardellicchio, N., Dell Atti, A., Di Leo, A., Maci, A., 2006. Heavy metals in marine sediments of Taranto Gulf (Ionian Sea, Southern Italy). Marine Chemistry 99, 227-235. Carman, C.M.I., Xiang-Dong, L., Gan, Z., Onyx, W.H.W., Yok-Sheung, L., 2007. Trace metal distribution in sediments of the Pearl River Estuary and the surrounding coastal area, South China: Environmental Pollution 147, 311-323. Esslemont G., 2000. Heavy metals in seawater, marine sediments and corals from the Townsville section, Great Barrier Reef Marine Park, Queensland. Marine Chemistry 71(3), 215-231. Glasby, G. P., Schulz, H. D., 1999. Eh, pH Diagrams for Mn, Fe, Co, Ni, Cu and As under Seawater Conditions: Application of Two New Type of Eh, pH Diagrams to the Study of Specific Problems in Marine Geochemistry. Aquatic Geochemistry 5, 227-248. Hedges, J. I., Clark, W. A., Cowie, G. L., 1988: Organic matter sources to the water column and surficial sediments of a marine bay. Limnology and Oceanography 33(5), 1116-1136. Majer A.P., Petti M.A.V., Corbisier T.N., Ribeiro A.P., Theophilo C.Y.S., de Lima Ferreira P.A. and Figueira R.C.L., 2014: Bioaccumulation of potentially toxic trace elements in benthic organisms of Admiralty Bay (King George Island, Antarctica). Marine Pollution Bulletin 79(1), 321-325. Mai Trong Nhuan, 2011: Survey on characteristics of geology, geodynamics, geological resources, geoenvironment and focasting geohazards of East Vietnam Sea from 30-100m water depth, scale 1:500.000. Achieved in Marine Natural Resources - Environment Survey Center. Naser, H.A., 2013: Assessment and management of heavy metal pollution in the marine environment of Arabian Gulf: A review. Marine Pollution Bulletin 72, 6-13. Nguyen Bieu, 1999: Survey on geology and mineral resouces in nearshore East Vietnam Sea (0-30 m water depth), scale 1:500.000. Achieved in Marine Natural Resources - Environment Survey Center. Pham Van Thanh, 2009: Report on environmental geology map of marine sediments of East Vietnam Sea (0-20 m water depth), scale 1:250.000. Project No. KC09.21/06-10. Achieved in Ministry of Science and Technology. Tran Nghi, 2004. Establishing the map of Quaternary formations of East Vietnam Sea and adjacent basin, scale 1:1.000.000. Project No. KC09-23. Achieved in Ministry of Science and Technology. Vu Truong Son, 2004. Environmental geochemistry of neashore sea from Rach Gia-Vung Tau. Doctor disertation on Geology. Achieve in VNU University of Science. Valavanidis, A., Vlachogianni, T., 2010. Metal pollution in ecosystems. Ecotoxicology studies and risk assessment in the marine environment. Sci. Adv. Environ. Toxicol. Ecot. Issues. chem-tox-ecotox. org/wp/wp-content/uploads/2010/01/02-Metals-17_01_2010. pdf [on line]. Vizzini S., Costa V., Tramati C., Gianguzza P., Mazzola A., 2013. Trophic transfer of trace elements in an isotopically constructed food chain from a semi-enclosed marine coastal area (Stagnone di Marsala, Sicily, Mediterranean). Archives of environmental contamination and toxicology 65(4), 642-653. Wang S., Jia Y., Wang S., Wang X., Wang H., Zhao Z., Liu B., 2010. Fractionation of heavy metals in shallow marine sediments from Jinzhou Bay, China. Journal of Environmental Sciences 22(1), 23-31. Canadian Council of Ministers of the Environment (CCME), 2002. Canadian sediment quality guidelines for the protection of aquatic life: Summary tables. Updated. In: Canadian Environmental Quality Guidelines, 1999: Canadian Council of Ministers of the Environment, Winnipeg. Helsinki Commission and Baltic Marine Environment Protection Commission, 2004. Heavy metal pollution to the Baltic sea in 2004. Baltic Sea Environment Proceedings, No. 108. Ministry of Natural Resources and Environment (MONRE), 2008. National technical regulation on coastal water quality - QCVN 10:2008/BTNMT. Ministry of Natural Resources and Environment (MONRE), 2011. Guideline of quantifying and regulation on analytical results of geological and mineral samples. Ministry of Natural Resources and Environment (MONRE), 2012a. National technical regulation on off-shore water quality - QCVN 44:2012/BTNMT. Ministry of Natural Resources and Environment (MONRE), 2012b. National technical regulation on sediment quality - QCVN 43 : 2012/BTNMT. CCOP:http://www.ccop.or.th/ Songthu Corporation: http://www.songthu.com.vn/